Validation of Picayo Training Module for Increasing Trust in Mental Health Experts on Adolescent - Fipti, Friska Ulfalia; Mahanani, Fatma Kusuma (Nusantara Journal of Behavioral and Social Science, 2022)
The lack of training media used as a source of information for content and functionally validated mental health experts in adolescents causes the low level of trust in mental health experts in adolescents. The objective of the study was to determine the validity of the PICAYO module to increase trust in mental health experts. A quantitative approach with a quasi-experimental design. Nonrandomized Pretest-Postest Control Group Design was chosen in this study. Students of SMA state 12 Semarang who have trust in mental health experts who have low scores were selected as research subjects. Subjects were divided into an experimental group (12 people) and a control group (14 people). The instrument used is a scale of trust in mental health experts. Validation was carried out through content validity and functional validity tests. Aiken's V technique was used to obtain content validity. The results obtained from the content validity test ranged from 0.75 to 0.90, which means that the PICAYO module has a moderate to very valid category. Functional validity was obtained through empirical testing with experimental methods. The research data were then processed using the Mann Whitney U Test technique with the help of data processing software. The results of the functional validity test showed that there were differences in the pretest and posttest scores in the experimental group, with a different test result of -3.960 with a significance of 0.000 (p less than 0.05). It was also found that the posttest score in the experimental group was superior to the control group, with a different test result of -2.580 with a significance level of 0.10 (p less than 0.05). Based on these results, it can be concluded that the PICAYO module is valid for increasing trust in mental health experts in adolescents.  Abstrak: Belum banyaknya media pelatihan yang digunakan sebagai sumber informasi terhadap ahli kesehatan mental yang tervalidasi secara isi dan fungsional pada remaja menyebabkan rendahnya tingkat kepercayaan terhadap ahli kesehatan mental pada remaja.Tujuan dari penelitian ini adalah untuk mengetahui validitas modul picayo untuk meningkatkan kepercayaan terhadap ahli kesehatan mental. Pendekatan kuantitatif dengan desain eksperimen kuasi Nonrandomized Pretest-Postest Control Group Desaign dipilih pada penelitian ini. Siswa SMA Negeri 12 Semarang yang memiliki kategori kepercayaan terhadap ahli kesehatan mental yang mempunya skor rendah dipilih sebagai subjek penelitian. Subjek terbagi menjadi kelompok eksperimen (12 orang) dan kelompok kontrol (14 orang). Instrumen yang digunakan adalah skala kepercayaan terhadap ahli kesehatan mental. Validasi dilakukan melalui uji validitas isi dan validitas fungsional. Teknik Aiken’s V digunakan untuk memperoleh validitas isi. Hasil yang didapatkan dari uji validitas isi berkisar antara 0,75 sampai dengan 0,90 dengan arti bahwa modul picayo memiliki kategori valid sedang hingga sangat valid. Validitas fungsional diperoleh melalui uji empirik dengan metode eksperimen. Data hasil penelitian kemudian diolah menggunakan teknik Mann Whitney U Test dengan bantuan software pengolah data. Hasil uji validitas fungsional menunjukkan terdapat perbedaan skor pretest dan posttest pada kelompok eksperimen, dengan hasil uji beda sebesar -3,960 dengan signifikansi 0,000 (p kurang dari 0,05). Didapatkan pula hasil skor posttestpadakelompokeksperimenlebihungguldibandingkandengankelompokkontrol,dengan hasil uji beda -2,580 dengan taraf signifikansi 0,10 (p kurang dari 0,05). Berdasarkan hasil tersebut, maka dapat ditarik kesimpulan bahwa modul picayo valid untuk meningkatkan kepercayaan terhadap ahli kesehatan mental padaremaja.